PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, DAN PERILAKU BELAJAR TERHADAP PEMAHAMAN AKUNTANSI (Studi Empiris Pada Mahasiswa Akuntansi Di Perguruan Tinggi Terakreditasi A Di Kota Semarang) - Nurul Fadhilah, 12.05.52.0179; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2016)
The aim of the research is to examine the effect of intellectual intelligence, emotional intelligence, spiritual intelligence and learning behavior towards understanding of accounting. This research was conducted on accounting students force in 2012 at A college accredited in Semarang. The data used are primary data. The sampling method used convenience sampling or sample the ease in determining the sample. The technique analytical used is multiple regression analysis. The results showed that the intellectual intelligence, emotional intelligence and learning behavior has positive effect to the understanding of accounting. Whereas spiritual intelligence had no effect on understanding of accounting.Keywords: Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence, Learning Behavior, Understanding Of Accounting